A New Approach to Prepare Efficient Blue AIE Emitters for Undoped OLEDs1. Issue 18 (24th March 2014) - Huang, Jing; Tang, Runli; Zhang, Tian; Li, Qianqian; Yu, Gui; Xie, Shuyi; Liu, Yunqi; Ye, Shanghui; Qin, Jingui; Li, Zhen
Abstract Two aggregation‐induced emission active luminogens (TPE–pTPA and TPE–mTPA) were successfully synthesized. For comparison, another six similar compounds were prepared. Because of the introduced hole‐dominated triphenylamine (TPA), fluorene groups with high luminous efficiency, and unconjugated linkages, the π conjugation length of the obtained luminogens is effectively restricted to ensure their blue emission. The undoped organic light‐emitting diodes based on TPE–pTPA and TPE–mTPA exhibited blue or deep‐blue emissions, low turn‐on voltages (3 V), and high electroluminescence efficiencies with Lmax, ηC, max, and ηP, max values of up to 26 697 cd m−2, 3.37 cd A−1, and 2.40 Lm W−1.